Some New Hermite–Hadamard-Type Inequalities Associated with Conformable Fractional Integrals and Their Applications. (23rd February 2020) - Iqbal, Arshad; Khan, Muhammad Adil; Ullah, Sana; Chu, Yu-Ming
Abstract : In this article, we establish some new Hermite–Hadamard-type inequalities involving the conformable fractional integrals. As applications, several inequalities for the approximation error in the midpoint formula and certain bivariate means are derived.